SYNTHESIS OF MERCAPTOETHYL CARBOXYLATE FROM FATTY ACID OF KAPOK SEED - Muhamad Fauzi, Irfan
Polyvinyl chloride (PVC) has a strategic potential to be developed in Indonesia because of its wide application and high production capacity. Although there are many benefits that can be taken, PVC is easily degraded by heat which results in changes in the properties of the polymer. Therefore, a thermal stabilizer is required for PVC to overcome its degradation during processing. Conventional stabilizers are made of lead-based materials. However, environmental issues have resulted in lead being replaced with organic tin, which is more environmentally friendly, one of which is from the mercaptide group. The stabilizer from the mercaptide group is produced in two stages, namely the synthesis of mercaptoethyl carboxylate and the synthesis of methyl tin mercapto carboxylate sulfide. The synthesis reaction of mercaptoethyl carboxylate is an esterification reaction between mercaptoethanol and free fatty acids. Commonly used free fatty acids come from pine trees. However, its availability is increasingly limited due to environmental damage. Therefore, it is necessary to look for other alternatives from nonfood ingredients so as not to compete with the existing food industry. One of the alternative free fatty acids that can be used is derived from kapok seed oil. Indonesia was once the largest producer of kapok fruit. However, there was a decline in export figures because kapok farmers no longer saw the potential of kapok plants. Utilization of fatty acids from kapok seeds can result in an increase in the return value of the kapok plant. The purpose of this study was to synthesize mercaptoethyl carboxylate from fatty acids of kapok seeds, to know and compare their characteristics, and to know the optimum operating conditions. The research is based on experiments at the Process Industrial Product Engineering Laboratory. The studies were carried out with different catalyst concentrations, excess mercaptoethanol, and temperatures. Acid number, SH content, percent recovery, and transparency were all used to evaluate synthesis performance. The acidity and clarity of all variants have a substantial impact. Variations in catalyst concentration and mercaptoethanol excess had a substantial impact on SH content and percent recovery, respectively. However, there are no substantial differences between temperatures of 70oC and 80oC. This study found that the optimal operating parameters include a 3% catalyst concentration, a 10% excess of mercaptoethanol, and a temperature of 80oC.